Polydatin Attenuates Neuronal Loss via Reducing Neuroinflammation and Oxidative Stress in Rat MCAO Models - Shah, Fawad Ali; Kury, Lina Al; Li, Tao; Zeb, Alam; Koh, Phil Ok; Liu, Fang; Zhou, Qiang; Hussain, Ishtiaq; Khan, Arif Ullah; Jiang, Yuhua; Li, Shupeng (Frontiers in Pharmacology, 2019)
Ischemic stroke is characterized by permanent or transient obstruction of blood flow, which initiates a cascading pathological process, starting from acute ATP loss and ionic imbalance to subsequent membrane depolarization, glutamate excitotoxicity, and calcium overload. These initial events are followed by neuroinflammation and oxidative stress, eventually causing neuronal neurosis and apoptosis. Complicated interplays exist between these steps happening across various stages, which not only represent the complicated nature of ischemic pathology but also warrant a detailed delineation of the underlying molecular mechanisms to develop better therapeutic options. In the present study, we examined the neuroprotective effects of polydatin against ischemic brain injury using a rat model of permanent middle cerebral artery occlusion (MCAO). Our results demonstrated that polydatin treatment reduced the infarction volume and mitigated the neurobehavioral deficits, sequentially rescued neuronal apoptosis. Ischemic stroke induced an elevation of neuroinflammation and reactive oxygen species, which could be attenuated by polydatin via the reduced activation of p38 mitogen-activated protein kinase and c-Jun N-terminal kinase. In addition, polydatin upregulated the endogenous antioxidant nuclear factor erythroid 2-related factor 2, heme oxygenase-1, the thioredoxin pathway, and eventually reversed ischemic-stroke-induced elevation of ROS and inflammation in ischemic cortical tissue. The diverse and broad actions of polydatin suggested that it could be a multiple targeting neuroprotective agent in ameliorating the detrimental effects of MCAO, such as neuroinflammation, oxidative stress, and neuronal apoptosis. As repetitive clinical trials of neuroprotectants targeting a single step of stroke pathological process have failed previously, our results suggested that a neuroprotective strategy of acting at different stages may be more advantageous to intervene in the vicious cycles in MCAO.